2016
DOI: 10.1111/jphp.12587
|View full text |Cite
|
Sign up to set email alerts
|

Dexamethasone – PAMAM dendrimer conjugates for retinal delivery: preparation, characterization and in vivo evaluation

Abstract: Current studies are focused on formulation improvement to enhance hydrolysis and clearance time.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
41
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(45 citation statements)
references
References 36 publications
(38 reference statements)
3
41
0
Order By: Relevance
“…The spectrum of PSPD shows that the signals at δ 2.0 ppm are associated with the methyl protons of DMMA (Figure S3, Supporting Information) . In the P 123 ‐Dex 1 H NMR spectrum (Figure S4, Supporting Information), Dex signals could be better visualized in the 5.0–8.0 ppm range . The above results suggested that the proposed structure was synthesized successfully.…”
Section: Resultsmentioning
confidence: 80%
“…The spectrum of PSPD shows that the signals at δ 2.0 ppm are associated with the methyl protons of DMMA (Figure S3, Supporting Information) . In the P 123 ‐Dex 1 H NMR spectrum (Figure S4, Supporting Information), Dex signals could be better visualized in the 5.0–8.0 ppm range . The above results suggested that the proposed structure was synthesized successfully.…”
Section: Resultsmentioning
confidence: 80%
“…Studies involving anionic PAMAM species confirmed a similar toxic effect towards bacterial membranes, however at higher concentrations compared to their cationic counterparts [21,45]. Interestingly, there are only few studies on eukaryotic membranes assessing anionic PAMAM dendrimers, but all reports indicate no or little toxicity even at concentrations up to 1 mg mL -1 (human corneal epithelial cells; human glioma cells) [49,68]. The different interaction kinetics of PAMAM G5 and PAMAM G4.5 observed in our study indicate different modes of penetration into the DPPG and DPPC lipid monolayers, which might be related to the distinctive toxicity behaviour of both PAMAM species reported in some of the studies mentioned above, and might be due to the lipid model used..…”
Section: Discussionmentioning
confidence: 92%
“…Interestingly, fewer studies have been carried out using anionic dendrimers despite their lower cytotoxicity [25,44], antimicrobial activity [21,45] and suitability as potential drug delivery agents [46,47]. Just recently, their advantages over the cationic counterparts have started to attract more interest in the research community and membrane interactions in vitro were studied with the view of their potential as an anionic drug carrier [48,49]. However, the molecular processes underlying their interactions with biomembranes and their lower cytotoxicity are still not understood and very few studies have been focussing on elucidating anionic PAMAM's interaction mechanism with model lipid membranes [50,51] or proteins [52,53] so far.…”
Section: Discussionmentioning
confidence: 99%
“…So far, they are still being tested at the in vitro stage for inhibition of VEGF expression with intravitreally administered antisense oligonucleotide compounds. [292][293][294][295][296] Novel ocular injection devices, such as the iTrack microcatheter (iScience Interventional), allow the administration of various medications in the suprachoroidal space to allow for a sequestered, sustained release of drug. Recently, a combination of bevacizumab and triamcinolone was delivered via the iTrack device to the submacular area in a pilot study of patients with chronic ME and HEs.…”
Section: Drug Delivery Strategiesmentioning
confidence: 99%